Male Red-crested Cardinal plumage coloration is associated with parental abilities and breeding performance - Segura, Luciano Noel (2019)
Avian plumage coloration deriving from carotenoid-based pigments is among the most honest signals of individual quality. It has been argued that females may differentially allocate resources based on mate attractiveness or quality, paying the costs of investing more in a current breeding attempt. We tested predictions of the differential allocation hypothesis on the natural variation of carotenoid-based plumage using the brightly red-colored head plumage of the Red-crested Cardinal (Paroaria coronata). It is to our knowledge the first time this hypothesis is tested on the natural variation of this pigment on a wild bird. We found that the brightness of the males’ red plumage patch is positively associated with their reproductive success and the nest defence they provide. We also found that brighter males invest less in their offspring (by delivering less food to their nestlings and poorly cleaning the nest) than duller males and, by contrast, females mated with brighter males invest more in parental care. Our results are consistent with the differential allocation hypothesis: differential allocation allowed breeding pairs with brighter males to produce more offspring, suggesting that it can be considered adaptive and should be included in studies of eco-evolutionary dynamics.